One-step synthesis of a visible-light driven C@N–TiO2 porous nanocomposite: Enhanced absorption, photocatalytic and photoelectrochemical performance. (January 2020) - Yu, Yanmin; Xia, Jianxin; Chen, Chen; Chen, Huiying; Geng, Junfeng; Li, Hua
Abstract: An economical and green synthetic method is reported for preparing N-doped TiO2 nanoparticles modified with carbon (denoted as C@N–TiO2 ) by abandoning additional carbon sources in the synthetic process but utilizing the carbon element contained in precursors. Full characterizations including XRD, TEM, Raman spectra, XPS, TG, FTIR, BET, CV, and LSV are performed to determine the composition, structure, morphology, optical and electronic properties of C@N–TiO2 . Methyl orange (MO), methylene blue (MB), and phenol are selected as photodegrading agent to evaluate the photocatalytic activity of the as-prepared product. Our results show that C@N–TiO2 displays superior dye-adsorption ability and photocatalytic activity under visible light than pure TiO2 . In addition, C@N–TiO2 exhibits much enhanced electrochemical properties, with a nine-fold improvement of photocurrent intensity as compared with pure TiO2 . Highlights: C@N–TiO2 composites are successfully synthesized via an in -situ approach. The composite displays enhanced photocatalytic degradation under visible light irradiation. The composite exhibits a nine-fold improvement of photocurrent intensity than TiO2 . C@N–TiO2 displays superior adsorption ability.